Conceptual design progress of advanced fusion neutron source. (21st December 2020) - Ochiai, K.; Sato, S.; Kondo, H.; Ohta, M.; Oyaidzu, M.; Nakamura, M.M.; Kwon, S.; Tanigawa, H.; Nozawa, T.; Kasugai, A.; Sakamoto, K.; Ishida, S.
Abstract: Based on the results of the IFMIF/EVEDA project in the broader approach (BA) activities, the conceptual design of the Advanced Fusion Neutron Source (A-FNS) to obtain irradiation data of DEMO blanket materials is under consideration in Japan. This paper describes the progress of the A-FNS conceptual design, which consists of a 40 MeV, 125 mA deuteron beam, a liquid lithium target system, and a test and post-irradiation test facilities. the main objectives of the A-FNS are the acquisition of RAFM irradiation data up to 2035 and the tritium recovery test on the blanket. In addition, it is expected to be used for various neutron researches. The technical design activities of the A-FNS are focused on improvement of the lithium target design, review of impurity criteria, remote handling, and irradiation application plan.